Effect of Disinfectants on the Hardness and Roughness of Reline Acrylic Resins - Andrea Azevedo, DDS;1 Ana Lucia Machado, DDS, MS, PhD;2 Carlos Eduardo (Journal of Prosthodontics, 2006)
Potential effects on hardness and roughness of a necessary and effective disinfecting regimen (1% sodium hypocholorite and 4% chlorhexidine) were investigated for two hard chairside reline resins versus a heat-polymerizing denture base acrylic resin.